Expert Workshop on Food Systems Resilience in Africa and Europe - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
The Long-term Europe-Africa Partnership for Food and Nutrition Security and Sustainable Agriculture (LEAP4FNSSA) has undertaken a study on Food Systems Resilience with the objective of making recommendations that could shape future policies in bi-regional (Africa-Europe) collaboration on research and innovation (R&I). University of Hohenheim led the Study Team, and has submitted the study report. The Experts Thematic Workshop is organized to provide an avenue for presentation and discussion of the findings of the study. The workshop will receive presentation of the study report, deliberate on the key outcomes and recommendations, and help to elaborate action steps, analysis, and foresight that could be used in advancing Europe-Africa partnership in Food and Nutrition Security and Sustainable Agriculture.